1975
DOI: 10.3758/bf03326811
|View full text |Cite
|
Sign up to set email alerts
|

Vibrissal anesthesia and suppression of irritable fighting in rats: A temporary duration of effect in experienced fighters

Abstract: Selected pairs of agressive rats fighting reliably and at relatively high levels were successively treated with lidocaine anesthesia of the vibrissal pads prior to each daily test session. The initial decrement in fighting was substantial, but after only three sessions pretest level of fighting was regained. Initial decrease in fighting of a second group following removal of all vibrissae was comparable to that produced by local anesthesia, but recovery of fighting to pret~st levels was slower and less complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
3

Year Published

1976
1976
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 6 publications
3
11
3
Order By: Relevance
“…On day 3, sniff latencies of the treatment category were similar to the controls. These results are in contrast to those of Thor and Ghiselli (1975) who found that the shock-induced fighting levels of experienced devibrissated rats never reached preoperative levels. Thor and Ghiselli (1975) found that experienced rats with vibrissal anaesthesia regained previous levels of footshock-induced fighting after only 3 sessions.…”
Section: Fighting Irz Experienced Fighter Micecontrasting
confidence: 85%
See 2 more Smart Citations
“…On day 3, sniff latencies of the treatment category were similar to the controls. These results are in contrast to those of Thor and Ghiselli (1975) who found that the shock-induced fighting levels of experienced devibrissated rats never reached preoperative levels. Thor and Ghiselli (1975) found that experienced rats with vibrissal anaesthesia regained previous levels of footshock-induced fighting after only 3 sessions.…”
Section: Fighting Irz Experienced Fighter Micecontrasting
confidence: 85%
“…Little evidence is available on this paradigm, but Ghiselli 8i Thor (1975) performed an interesting study comparing shock-induced fighting in control, native blind, anosmic and devibrissated (with or without local anacsthesia of mystacid area) male 'hooded' rats. They found that both olfaction and touch were important in the control of shock-induced fighting in rats.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we could not determine whether those animals had judged stimulus position before orienting, we note that refined rostrocaudal information is necessary if a rat is to orient rapidly following contact without further search. Although the current study does not attempt to characterize the role of angular perception during natural activity, we note that the vibrissae are involved in activities with complex spatial demands, such as navigation [14,44], aggression [56], and swimming [57] (for a general review of the classic literature, see Gustafson and Felbain-Keramidas [7]). This ubiquitous role suggests that these sensorimotor organs paint a richer picture of the tactile world than would be possible from binary detection alone.…”
Section: Discussionmentioning
confidence: 99%
“…The increased biting after isolation has been observed both in conspecific test situations [Hutzell and Knutson, 19721 and in response to human handling [Hatch et al, 1963;Moyer and Korn, 19651. Another motivating stimulus of the consociate modulator may consist of the high frequency rhythmic twitches of the vibrissae of the opponent [Komisaruk, 19701. They may function to identify the opponent as a conspecific. When these twitches are abolished by lidocaine anesthesia of the face, a rat is more likely to be bitten (ie, receive a lunge-and-bite attack) on the face during shock-induced fighting [Thor and Ghiselli, 1975;Blanchard et al, 1977b;Kanki and Adams, 19781.…”
Section: Releasing and Directing Stimuli Of Submissionmentioning
confidence: 99%